The revolt of the masses - Ortega y Gasset, José 1883-1955 (Routledge, 2022)
Intro -- Half Title -- Title Page -- Copyright Page -- Original Title Page -- Original Copyright Page -- Prefatory Note -- Table of Contents -- I The Coming of the Masses -- II The Rise of the Historic Level -- III The Height of the Times -- IV The Increase of Life -- V A Statistical Fact -- VI The Dissection of the Mass-Man Begins -- VII Noble Life and Common life, or Effort and Inertia -- VIII Why the Masses Intervene in Everything, and Why Their Intervention Is Solely by Violence -- IX The Primitive and the Technical -- X Primitivism and History -- XI The Self-Satisfied Age -- XII The Barbarism of 'Specialization' -- XIII The Greatest Danger, the State -- XIV Who Rules in the World? -- XV We Arrive at the Real Question
First published in Spanish in 1930. First published in this edition in 1961 by George Allen & Unwin Ltd.